2017
DOI: 10.5334/gjgl.183
|View full text |Cite
|
Sign up to set email alerts
|

Internally-headed relative clauses in sign languages

Abstract: This chapter considers relative clause data from sign languages in light of their variation with respect to basic word order, nonmanual marking, and presence/absence of internally-headed and externally-headed relative clauses. Syntactically, a double merge cartographic model (Cinque 2005a;, following Brunelli (2011), is adopted. The differences across sign languages are suggested to result from differences in raising requirements with respect to the relative clauses themselves and with respect to their heads, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 36 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…In the vast majority of sign languages, relative clauses are signaled through the use of specific manual and/or non-manual markers, the only exception being JSL, where according to Penner et al (2019) there is no marking whatsoever signaling relativization. For example, ASL RCs are signaled through backward head tilt, raised eyebrows, and tensed upper lip (Wilbur, 2017).…”
Section: Relative Clauses In Sign Languagesmentioning
confidence: 99%
“…In the vast majority of sign languages, relative clauses are signaled through the use of specific manual and/or non-manual markers, the only exception being JSL, where according to Penner et al (2019) there is no marking whatsoever signaling relativization. For example, ASL RCs are signaled through backward head tilt, raised eyebrows, and tensed upper lip (Wilbur, 2017).…”
Section: Relative Clauses In Sign Languagesmentioning
confidence: 99%
“…The use of both internally headed and externally headed strategies in TİD are not unique to this sign language, ASL has been observed to have both constructions as well (Wilbur, 2017). In this paper we showed that strategy of doubling HN is slightly more preferred over internally and externally headed strategy in TİD.…”
Section: Discussionmentioning
confidence: 54%
“…Kubus (2016) has already hypothesized that squint has grammaticized from a discourse marking element into a syntactic one. However, squint does not seem to be syntactic marker for RCs in ASL (Wilbur, 2017) and DGS (Pfau & Steinbach, 2005). The competition between squint and brow raise can be explained at the syntactic level, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…indigenous languages of North America, Tibeto-Burman languages, signed languages), the body of literature informing our understanding of this clause type is still relatively small. Languages which have been reported to have IHRCs include Navajo (Platero 1974), Lakhota (Williamson 1987), Diegueño (Gorbet 1976), Mojave (Munro 1976), Japanese (Hiraiwai 2017), and a variety of signed languages (Wilbur 2017). IHRCs are also quite prevalent in Tibeto-Burman languages (Dryer 2008, Subbarao 2008, such as Tenyidie (Subbarao and Kevichüsa 1999), Sema (Subbarao and Kevichüsa 2005), Qiang (Huang 2008), and Hakha Chin (Kathol and VanBik 1999).…”
Section: Introductionmentioning
confidence: 99%